Menggagas Mekanisme Perlindungan Anak Korban Kekerasan Seksual di Provinsi Aceh - Nursiti Nursiti (Kanun Jurnal Ilmu Hukum, 2011)
ABSTRACT: The Act Number 23, 2002 regarding the Child Protection is a policy issued to provide a protection on children as a part of responsibility of the state, government and society. In the Act also states the policy making sure that the children can be protection from all kinds of abuse including sexual abuse. Based on the data from the institution aiding the children in Aceh, recently this case increases steadily. Theefore, in terms of protecting them, it is important to instigate the mechanism in dealing with the case comprehensively in order to protect the children. Inspiring the Protection on Children as a Sexual Abuse Victims in Aceh Province